2020
DOI: 10.3390/rs12091426
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the CMORPH and GPM IMERG Products over the United Arab Emirates

Abstract: Satellite-based precipitation products are becoming available at very high temporal and spatial resolutions, which has accelerated their use in various hydro-meteorological and hydro-climatological applications. Because the quantitative accuracy of such products is affected by numerous factors related to atmospheric and terrain properties, validating them over different regions and environments is needed. This study investigated the performance of two high-resolution global satellite-based precipitation produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 59 publications
(76 reference statements)
6
29
1
Order By: Relevance
“…The Q-Q plots of the modeled and observed AMS quantiles show that the Gumbel distribution underestimates the lower quantiles and overestimates the higher quantiles in all of the metropolitan areas (Figure 7). Many validation studies that were conducted to assess the remotely sensed precipitation observed that the products underestimate heavy precipitation and overestimate light to medium precipitation [20,[34][35][36], which is consistent with the results shown in Figure 7, with the exception of McAllen (Figure 7D). McAllen has the best fit and the lowest normalized root mean square error, while the worst fit was observed in Dallas-Fortworth, with a normalized root mean square error of 32%.…”
Section: Fitting the Gumbel Distributionsupporting
confidence: 83%
“…The Q-Q plots of the modeled and observed AMS quantiles show that the Gumbel distribution underestimates the lower quantiles and overestimates the higher quantiles in all of the metropolitan areas (Figure 7). Many validation studies that were conducted to assess the remotely sensed precipitation observed that the products underestimate heavy precipitation and overestimate light to medium precipitation [20,[34][35][36], which is consistent with the results shown in Figure 7, with the exception of McAllen (Figure 7D). McAllen has the best fit and the lowest normalized root mean square error, while the worst fit was observed in Dallas-Fortworth, with a normalized root mean square error of 32%.…”
Section: Fitting the Gumbel Distributionsupporting
confidence: 83%
“…To our knowledge, IMERG has not yet been compared with the Climate Prediction Center MORPHing (CMORPH, Joyce et al ., 2004) dataset in the MC. Studies of IMERG and CMORPH in other regions show no clear evidence that one systematically outperforms the other in detecting extreme precipitation (Wei et al ., 2018; Lee et al ., 2019; Alsumaiti et al ., 2020; Xiao et al ., 2020). A recent study using nearly 20 years of gauge precipitation from Singapore, and taking into account their spatial sampling error, found that IMERG accurately represents extreme precipitation in this region (Mandapaka and Lo, 2020).…”
Section: Datamentioning
confidence: 99%
“…In general, the Early product reports the highest estimates while the Final product provides the lowest estimates. This is expected, as adjustment using climatological records would result in reduced estimates in dry regions (Alsumaiti et al 2020). The temporal patterns are generally similar.…”
Section: Rainfall Datamentioning
confidence: 73%
“…The low spatial and temporal resolutions and low quality of precipitation data are considered to be major challenges in many regions across the globe, including the Arabian Peninsula (Hussein et al 2020). The high quality, highresolution global satellite precipitation products that recently became available can fill this gap and provide accurate input for many applications, including water resources planning and management, hydrologic modeling and forecasting, design of hydraulic structures, and flood, drought, and landslide analysis and forecasting (Sharif et al 2017;Alsumaiti et al 2020).…”
Section: Introductionmentioning
confidence: 99%